Awareness of Health Policies and Risks Regarding Tobacco Smoking Among School Teachers in Pakistan - Maria Malik; Ashok Kumar; Deepa Mohan Lal; Wasfa Farooq; Kaneez Zehra; Ali Hamza Khan; Hamza Usman; Sajjad Ali; Nadeem Rizvi (ziauddin University, 2020)
Background: The phenomenon of smoking among schoolchildren has been observed to stem from lenient attitudes of teachers towards smoking. Smoking, a health hazard, proven over years of research, leads to increase in morbidity and mortality rates. This study determined the role of school policies and teacher attitudes towards the perception and adoption of smoking habits by students of private and public schools. Method: This was a cross-sectional study in which 632 school personnel in various private and public schools of South Karachi filled a questionnaire. Informed consent was obtained from all participants; ethical approval for this study was obtained from the Ethical Review Committee of JPMC before the study was conducted. Data was collected via survey forms after consent from individuals. Statistical analysis was done using SPSS v.17. Results: The prevalence of teacher smoking within school premises was found to be 8.8% and 5.9% in private and public sectors, respectively. A significant difference was found between the school policies enforced in private and government schools against personnel found smoking (p=0.00016). Even though private school personnel smoked more in school premises than government but 32.6% of private school teachers felt responsible for teaching about health compared to only 21.5% public school teachers (p=0.0072). Conclusion: There is a pressing need for awareness and education of teachers regarding their attitude towards smoking on school grounds and its significant link with students adopting smoking. Other exposures and risk factors influencing student tobacco usage needs to be studied in more depth.